An overview of exposure to ethanol-containing substances and ethanol intoxication in children based on three illustrated cases - Kam Lun Hon; Alexander KC Leung; Eddie Cheung; Bryan Lee; Michelle MC Tsang; Alcy R Torres (BioExcel Publishing Ltd, 2018)
Alcohol addiction and intoxication are major health problems worldwide. Acute alcohol intoxication is well reported in adults and adolescents but less frequently reported in children of younger ages. We report three anonymized cases of pediatric ethanol exposure and illustrate the different mechanisms of intoxication. In all cases, a focused history is the key to prompt diagnosis and timely management. Physicians should be aware of this potential poison in children presented with acute confusional or encephalopathic state. In contrast, neonates with ethanol intoxication may present with nonspecific gastrointestinal symptomatology. Urgent exclusion of sepsis, electrolyte imbalance, drug intoxication, and surgical abdominal condition is critical. Using these illustrated cases, we performed a narrative literature review on issues of exposure to ethanol-containing substances and ethanol intoxication in children. In conclusion, a high level of suspicion and interrogation on ethanol or substance use are essential particularly in the lactating mother for an accurate and timely diagnosis of ethanol intoxication to be made.